Evaluation of Radiation-induced Xerostomia in Patients with Nasopharyngeal Carcinomas - Parnian Alizadeh Oskoee; Farshad Seyyednejhad; Narmin Mohammadi; Siavash Savadi Oskoee; Niloofar Mofidi (Tabriz University of Medical Sciences, 2007)
Background and aims. Salivary glands are extremely susceptible to radiation injuries. The aim of this study was to evaluate radiation-induced xerostomia in patients with nasopharyngeal carcinomas, referring to Tabriz Imam Khomeini Hospital in 2005-2006. Materials and methods. Thirty patients with nasopharyngeal carcinomas, who received conventional radiotherapy, were included in the present study. The patients' unstimulated saliva samples were collected at three intervals, i.e. before treatment, 3 weeks after the initiation of treatment and at the end of treatment by spitting, and measured with a graduated pipette. Results. The differences in the mean values of the patients' salivary flow rates at three afore-mentioned intervals were statistically significant (p< 0.001). Two-by-two comparison of the mean values of salivary flow rates of all the patients and of males and females, carried out separately, demonstrated statistically significant differences (p< 0.0025). However, there were no statistically significant differences between males and females before treatment (p = 0.723), 3 weeks after the initiation of treatment (p = 0.724) and at the end of treatment (p = 0.595). There were no statistically significant relationships between age and a decrease in salivary flow rate in the total sample (p = 0.76, r = -0.057), in males (p = 0.96, r = 0.011) and in females (p = 0.539, r = -0.208). Conclusion. Conventional radiotherapy results in severe xerostomia in 3 weeks in patients with nasopharyngeal carcinomas. Age and sex do not influence radiotherapy-induced xerostomia.